Effects of Red Dragon Fruit Puree Application on Physicochemical Properties of Selected Bakery Products - Ignasius Radix A. P. Jati; Erni Setijawaty; Ratna Chrismiari Purwestri (Applied Sciences)
Bakery products are a popular staple food made from wheat flour and other ingredients. Common bread-making methods include baking, steaming, and frying. Recent trends focus on developing value-added bakery products by incorporating various health-promoting ingredients like fruit. Dragon fruit can be used in bread formulations due to its high fiber, bioactive content, and antioxidant activity. However, adding red dragon fruit can also be challenging in obtaining a high-quality bakery product because it will affect the physicochemical and sensory properties. Therefore, this study aims to investigate the effects of different red dragon fruit puree concentrations on the physicochemical and sensory properties of bread made with red dragon fruit. Three bakery products were made: white bread, steamed buns, and donuts. The red dragon fruit puree concentrations were 10%, 20%, 30%, 40%, 50%, and 60%, respectively. The treatment was repeated four times. Meanwhile, the analyses included moisture content, specific volume, hardness, springiness, cohesiveness, color, phenolic, DPPH, superoxide radical scavenging activity, and sensory properties. The presence of red dragon fruit puree increased the moisture content of white bread (0.3% to 2.1%), steamed buns (1.75% to 18.21%), and donuts (2.30% to 13.81%). Meanwhile, the presence of the puree decreased the capability of bread to expand, which ranged from 4.07 to 2.82 cm3/g for white bread, 3.14 to 2.78 cm3/g for steamed buns, and 3.47 to 2.87 cm3/g for donuts, resulting in a decrease in specific volume. The concentration of red dragon fruit puree also plays an important role in increasing the hardness and cohesiveness and decreasing springiness. The increase in red dragon fruit puree concentration affects the color parameters. Furthermore, the presence of red dragon fruit puree can maintain its high phenolic content, which was 15.25–59.11 mg GAE/100 g for white bread, 17.98–59.82 mg GAE/100 g for steamed buns, and 11.56–46.33 mg GAE/100 g for donuts, and dietary fiber, which was 1.32–2.03% for white bread, steamed buns 1.27–1.96%, and donuts 1.27–1.95%. Furthermore, the higher concentration of red dragon fruit puree contributes to higher phenolic and dietary fiber content. Bakery products could be developed as functional food, as reflected by their high antioxidant activity. Meanwhile, the sensory tests revealed that panelists could accept all three products.